2009
DOI: 10.1002/jnr.22121
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal expression of the proteolipid protein gene in the medulla of the mouse

Abstract: The proteolipid protein (PLP) gene (Plp) encodes the major myelin proteins, PLP and DM20. Expression of Plp occurs predominantly in oligodendrocytes, but evidence is accumulating that this gene is also expressed in neurons. In earlier studies, we demonstrated that myelin-deficient (MD) rats, which carry a mutation in the Plp gene, exhibit lethal hypoxic ventilatory depression. Furthermore, we found that, in the MD rat, PLP accumulated in neuronal cell bodies in the medulla oblongata. In the current study, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 38 publications
6
23
0
3
Order By: Relevance
“…2E, arrows). The EGFP low cells in PLP-EGFP mice likely represent brainstem neurons, as previously described for these mice (55). We next examined the relationship of Olig2 expression to EGFP expression and cellular vacuolation.…”
Section: Neurovirulent and Nonneurovirulent Ecotropic Mlvs Efficientlmentioning
confidence: 91%
See 1 more Smart Citation
“…2E, arrows). The EGFP low cells in PLP-EGFP mice likely represent brainstem neurons, as previously described for these mice (55). We next examined the relationship of Olig2 expression to EGFP expression and cellular vacuolation.…”
Section: Neurovirulent and Nonneurovirulent Ecotropic Mlvs Efficientlmentioning
confidence: 91%
“…In addition, certain brainstem neurons express much lower levels of EGFP (EGFPlow), allowing the two EGFP populations to be distinguished from one another (Fig. 2E to G) (55). Moreover, this differential expression facilitated a coincident morphological assessment of OLs and vulnerable neurons.…”
Section: Neurovirulent and Nonneurovirulent Ecotropic Mlvs Efficientlmentioning
confidence: 97%
“…Previous studies have shown that the plp gene promoter is also active in some neuronal cells (Bongarzone et al, 1999;Miller et al, 2009;Gó mez-Casati et al, 2010). To investigate the possibility that transgenic TAG-1 protein may also be expressed in neurons, we performed a series of immunofluorescence experiments in vivo and in vitro.…”
Section: Generation Of Transgenic Mice That Express the Rat Homolog Omentioning
confidence: 99%
“…M6b interacts with the serotonin transporter and promote its expression on the cell surface (Fjorback et al, 2009) shown that PLP/DM20 is predominately expressed in oligodendrocytes. Although resent studies revealed that a splicing isoform of PLP/DM20 (sr-PLP/sr-DM20) is expressed in the mouse cortical neuron from E13 to P7 (Jacobs et al, 2003;Miller et al, 2009), anti-sr-PLP/DM20 antibody did not label axon tracts. The authors discussed that localization of this neuronal isoform is subcellularly restricted to the cell body of neurons.…”
Section: Functional Domains Of M6a For the Axonal Growthmentioning
confidence: 99%
“…Although PLP/DM20 has been believed as the main component of the myelin and solely expressed by oligodendrocytes, a recent study reports neuronal expression of a splicing isoform of PLP/DM20 in neurons (Miller 2009). To evaluate the contribution of PLP/DM20 in formation of the CC bundle, we made M6a-/-M6b-/Y PLP-/Y triple knockout mice.…”
Section: Development Of the CC In The M6a-/-m6b-/y Plp-/y Triple Knocmentioning
confidence: 99%